2022
DOI: 10.1001/jamacardio.2022.2825
|View full text |Cite|
|
Sign up to set email alerts
|

Sex Differences in Atrial Fibrillation Risk

Abstract: ImportanceWomen have a lower incidence of atrial fibrillation (AF) compared with men in several studies, but it is unclear whether this sex difference is independent of sex differences in prevalent cardiovascular disease (CVD), body size, and other risk factors.ObjectiveTo examine sex differences in AF incidence and whether AF risk factors differ by sex in a contemporary cohort of men and women without prevalent CVD.Design, Setting, and ParticipantsThis was a prospective cohort analysis within the Vitamin D an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…The next, another possible explanation is that 80% of the patients in the population were male atrial fibrillation. There were gender differences in AF patients [24,25] . Cheng [26] conducted a meta-analysis of 151370 patients, 34% of whom were women, and discovered that women who underwent catheter ablation of AF may have a higher risk of stroke/TIA and major complications than men, and that genetic, vascular biology, hormonal, or thromboembolic factors that differ between men and women may lead to a higher risk of complications [27,28] .…”
Section: Discussionmentioning
confidence: 92%
“…The next, another possible explanation is that 80% of the patients in the population were male atrial fibrillation. There were gender differences in AF patients [24,25] . Cheng [26] conducted a meta-analysis of 151370 patients, 34% of whom were women, and discovered that women who underwent catheter ablation of AF may have a higher risk of stroke/TIA and major complications than men, and that genetic, vascular biology, hormonal, or thromboembolic factors that differ between men and women may lead to a higher risk of complications [27,28] .…”
Section: Discussionmentioning
confidence: 92%
“…However, we observed high correlations between self-reported and directly measured variables, such as weight and BMI, in a subset of VITAL participants enrolled in the Clinical Translational Science Center. 47 Fifth, participants with morbid obesity were underrepresented in the study population; thus, the proportion presenting with paroxysmal AF may, to some degree, be an overestimate of the general population. Sixth, standardized echocardiograms were not systematically collected in this cohort, and, therefore, we were unable to perform a formal mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologic mechanisms involved in the differential risk for men and women per decade are unclear and may include increased pregnancies due to repeated hormonal exposure and other metabolic factors ( 32 ); including earlier age at menopause associated with the anti-inflammatory effects of estrogens ( 33 ), DM has been associated with incident AF in women but not in men ( 34 ), and OSA is more frequent in women older than 55 years ( 35 ). Siddiqi et al reported that women are at higher risk for incident AF than men when BMI is analyzed in stratified models ( 36 ). Although the accumulation of comorbidities increases the chance of developing risk factors, some factors such as family history of AF, ethnicity and genetic risk profile should be considered to explain the increased AF risk in older women ( 37 ).…”
Section: Discussionmentioning
confidence: 99%